1988
DOI: 10.1177/000456328802500411
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and Plasma Creatine Kinase Activity

Abstract: SUMMARY.Plasma creatine kinase (CK) activity and lean body mass (LBM) (by anthropometry) were measured in 120 women (20-82 years) and 70 men (20-82 years). Plasma CK activity and LBM was higher in men than in women. In men plasma CK activity was significantly correlated (product moment correlation coefficient) with LBM and negatively with age. In women plasma CK activity was significantly correlated with age. Partial correlation coefficient calculation showed a significant correlation between plasma CK and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…CK levels are higher in subjects with greater lean body mass [16] so it is possible that subjects with lower baseline CK had less muscle mass and would therefore receive a higher dose of statin per kg of muscle thereby producing more muscle injury. There was no difference in body weight or BMI between the two groups making this possibility unlikely although we do not have a better estimate of skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…CK levels are higher in subjects with greater lean body mass [16] so it is possible that subjects with lower baseline CK had less muscle mass and would therefore receive a higher dose of statin per kg of muscle thereby producing more muscle injury. There was no difference in body weight or BMI between the two groups making this possibility unlikely although we do not have a better estimate of skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, larger breed rabbits demonstrated a higher CK and ALT activity and a higher creatinine serum concentration than smaller breed rabbits. And since in people, CK is markedly influenced by the organ mass, a similar explanation could be assumed for this finding in the rabbits. Body weight and lean body mass are also positively correlated with serum creatinine levels in people, and we therefore assumed a similar condition for the different rabbit breed size categories.…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, the pace was moderate and the duration was shorter. Swaminathan et al (10) identified a significant correlation between lean body mass and serum CK activity. Therefore, the absence of the expected increase in serum CK may be attributed to the gender of the subjects, since female runners have less lean body mass than male runners.…”
Section: Discussionmentioning
confidence: 98%